Martha Nussbaum’s “world citizen,” original sin, and a purpose to teaching the humanities - Sansom, Dennis (International journal of Christianity & education, 2024)
An Augustinian understanding of original sin can significantly contribute to the purpose of the teaching of the humanities. It helps at the point where Martha Nussbaum’s understanding of the humanities is inconsistent. She argues that the humanities should cultivate a “world citizen,” that is, a people aspiring towards a universal mindset, appreciating and incorporating the great diversity of cultural values and histories, but who also must rid themselves of the shackles of their own tradition and authority to reach this world citizenship. However, her “world citizen” ends up imposing the values shaped by the Western enlightenment on what to consider important to study about these diverse cultures and histories. Instead, the humanities should clarify the human experience, by showing how all people in all cultures struggle with the same problem—the world is not the way it is supposed to be; we do not know how to fix it, but we must morally improve it. St. Augustine’s teaching on original sin clarifies the cause and effect of the human experience and, thereby, provides a metaphysical basis for the humanities’ agenda to describe the human experience across times and culture.